The future of diets and hunger in South East Asia under climate change and alternative investment scenarios - Cenacchi, Nicola; Dunston, Shahnila; Sulser, Timothy B.; Wiebe, Keith D.; Willenbockel, Dirk (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
Despite enjoying strong economic growth in the last few decades, Southeast Asia still faces challenges to food security, with high levels of stunting across countries in the region. Agricultural production is likely to see large impacts from climate change, including sea-level rise, droughts, and floods. The climate threat compounds pressures onto the food systems coming from the rapid demographic and income trends. Population across the region may grow by 25% between 2010 and 2050, and average income per capita may see a fourfold increase in the same period. In absence of climate impacts, growth in agricultural productivity is estimated to bring about an increase in production of over 50% between 2020 and 2050, with positive effects on the availability of kilocalories, and increased consumption of animal products. However, the projected climate impacts are expected to hit most of the crops in the region, especially cereals. Per capita income in 2050 may be negatively affected compared to a scenario without climate shocks. The resulting decrease in total calories availability translates into an increase in population at risk of hunger across the region and by country. We show that enhanced investments in public international agricultural R&D have the potential to improve yields despite the long-term negative effects of climate shocks, and when combined with increased research efficiency they may even offset climate impacts on food security across the region.